CHRISTIAN PHILOSOPHERS OF THE WEST ABOUT THE “COLD WAR”, TOTALITARIANISM AND COMMUNISM: COMPARATIVE ANALYSIS OF REINHOLD NIEBUHR’S AND GIORGIO LA PIRA’S CONCEPTS - T. V. Zonova (Сравнительная политика, 2015)
The author examines the legacy of two great Christian thinkers, the American Reinhold Niebuhr and the Italian Giorgio La Pira, both very influential during the Cold War. Niebuhr was a Protestant theologian and political adviser to the American establishment. The Mayor of Florence, La Pira, was a prominent Italian statesman and an eminent Catholic thinker. The author analyzes their views on international relations, in particularly on the western policy towards the Soviet Union, the use of nuclear weapons, the war in Vietnam and communism. The legacy of two thinkers is highly topical in front of the ethical dimension of choices needed in international politics today.